The price of scarlet : poems - Noll, Brianna (University Press of Kentucky : The University Press of Kentucky, 2017)
"A honeycomb long vacated by honeybees still possesses an "echo of the swarm, / a lingering song." Living things are made and make themselves: "My bones came first. / Like long needles, / they knitted muscle / and tendon / and tissue and skin. / Filled themselves / with marrow." In her debut collection, Brianna Noll fuses the scientific and fantastic, posing probing questions that explore the paradoxes of experience. Interweaving themes of creation, art, and nature, the poet gives voice to animate and inanimate figures such as woolly mammoths, star-nosed moles, cells, mylar balloons, and puzzle boxes. Her vivid poems obscure the line between what is literal and what is figurative. The result is alchemic and ethereal--each verse intricately layered with sharp observation as well as emotional and intellectual exploration and questioning. Collectively, the poems draw significantly on Japanese culture and language in their imagery, with cultural nuances and implications embedded in words and expressions. They tend to be tied, not to subjects, but to ways of seeing and considering the world. Noll's lyrical voice reflects a curious and imaginative approach that results in tight poems, typically enjambed, which build together into a thoughtful collection. Her work offers ways of seeing and considering the world that exceed our lived experience, begging the reader to consider how far we are willing to go when faced with roadblocks, doubts, and uncertainties"--